Board Size and Firm Performance: The Moderating Role of Female Representation - Hendra Wijaya; Gesti Memarista (Institute of Research and Community Outreach - Petra Christian University, 2024)
This research aims to investigate the commissioner’s number of boards on the Indonesian go-public company’s performance. The disparity in types of gender begs the question of whether the applicability of women’s governance may lead to firm performance. So, the women's presence on that effect as the moderating factor is also examined and analyzed using panel data regression and ordinary least squares in this research. The study's samples are non-financial firms from 2015 until 2019, with 1210 observations. The commissioner's number of boards significantly affects Tobin's q and the market-to-book value ratio as the business performance measurement. Yet, the women’s board of commissioner’s proportion as the moderating factor did not affect the relationship between the commissioner's number of boards and the Indonesian go-public company's performance because of the small number of women on the board. It remains negligible since the dominant gender in the board of commissioners is men in Indonesian non-financial go-public companies, so the women directors may not improve the company’s performance. This study will help various businesses in various sectors by shedding light on the ideal board size for boosting productivity. It also acknowledges the significance of gender diversity on boards so that companies may make educated decisions about their boards' makeup and governance procedures. Given that women make up the minority of CEOs, policymakers will utilize these findings to create rules and directives that support gender diversity on boards and enhance business performance.